If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=j/3-6
We move all terms to the left:
2-(j/3-6)=0
We get rid of parentheses
-j/3+6+2=0
We multiply all the terms by the denominator
-j+6*3+2*3=0
We add all the numbers together, and all the variables
-1j+24=0
We move all terms containing j to the left, all other terms to the right
-j=-24
j=-24/-1
j=+24
| 45x-14x-2=91 | | w/8=-59 | | 7(d+86)=-14 | | 14+12y=-16=9y | | x+4.5x=1525 | | -50=-v/9 | | 4+9c=31 | | 12x+36=8x+100 | | 8(t+4)=96 | | (x/24)*29=18 | | x+5x=1525 | | 23x-5(3x+)=2x+2 | | 74=5k-11 | | n-9/6=9 | | 74=5k−11 | | v/9-35=-33 | | Q=4q+(76-10) | | 7(q+2)=35 | | 6y-4y+5=45 | | 100+12x-20=180 | | j+20/3=10 | | -2+-2d=-12 | | 36=1/36b | | 4u−12=4 | | 6.5x=1450 | | 81=–4v–5v | | 42x=3/4 | | h+19/7=8 | | u3+ 13=15 | | 20=g | | u/5+63=69 | | 16.5=1-0.25x |